Teknologi Tepat Guna Inovasi Alat Pencacah Rumput Sederhana Untuk Meningkatkan Efisiensi Pembuatan Pakan Ternak - Burhanuddin, Achmad Bintang; Wibowo, Rafi Hakim; Fajariya, Hurriya Nur; Rachmanda, Adis Dewanti; Sri Diyanti, Daffa Dwi (Bhumiputra: Jurnal Penelitian dan Pengabdian Masyarakat Global, 2025)
Livestock feed problems in rural areas are often faced by farmers, especially in terms of processing forage that requires chopping. In Candiwatu Village, the grass chopping process is still done manually which requires a long time, a lot of energy, and uneven cutting results. This community service activity aims to apply appropriate technology in the form of a simple grass chopper based on an iron barrel and dynamo. This innovation is designed to be easy to use, energy efficient, and efficient in its use by local farmers. The method of implementing activities includes a needs survey, tool design, training in use, and evaluation of results in the field. The implementation results show that this tool is able to speed up the grass chopping process up to three times compared to traditional methods, as well as reduce farmer fatigue and increase work time efficiency. This activity also encourages the community's spirit of mutual cooperation and serves as an example of the effective application of simple technology to support the productivity of village farms.